Three essays on corporate finance - Zhang, Li (2019)
In the first chapter, I study mutual funds’ exit decisions after voting at shareholder meetings. The results show that funds wining contentious votes at the meeting are more likely to exit the firm. This is consistent with that mutual funds seek to improve firm value by opposing management at the meeting, and then realize their gains and exit after winning. The second chapter studies the conflicts between equity holders and bond holders on managerial incentives. I find that firms with dual holders (institutional investors who simultaneously hold equity and bond of the firm) implement compensation policies with lower CEO Vega than firms with pure equity holders. The effect is stronger when the aggregate equity/bond holdings by dual holders are larger. The third chapter studies shareholder-bondholder conflicts on corporate social responsibility (CSR). I find that firms with dual holders have higher CSR ratings, and the effect is stronger when the dual holders’ equity/bond holdings on the firm are larger. It reveals bond holders prefer CSR more than equity holders and affect firm policies in this direction.